2015
DOI: 10.1039/c4ob02252a
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the contributions of hydrogen-bonding interactions to the activity of native and non-native ligands in the quorum-sensing receptor LasR

Abstract: Quorum sensing (QS) via the synthesis and detection of N-acyl L-homoserine lactone (AHL) signals regulates important pathogenic and mutualistic phenotypes in many bacteria. Over the past two decades, the development of non-native molecules that modulate this cell-cell signaling process has become an active area of research. The majority of these compounds were designed for block binding of the native AHL signal to its cognate LuxR-type receptor, and much effort has focused on LasR in the opportunistic pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 68 publications
6
25
0
Order By: Relevance
“…2D). Our results join previous findings suggesting that autoinducer acyl side chain length is particularly important in dictating the stimulation of LasR activity (36) and recent work cataloging hydrogen-bonding interactions in the LasR LBD critical for LasR activation and inhibition (37,38).…”
Section: Impact Of Oxidative Stress On the Lasr Ligand Binding Domainsupporting
confidence: 89%
“…2D). Our results join previous findings suggesting that autoinducer acyl side chain length is particularly important in dictating the stimulation of LasR activity (36) and recent work cataloging hydrogen-bonding interactions in the LasR LBD critical for LasR activation and inhibition (37,38).…”
Section: Impact Of Oxidative Stress On the Lasr Ligand Binding Domainsupporting
confidence: 89%
“…Subsequent mutational analyses revealed that modification of a single LasR residue, Trp60, that hydrogen bonds with the carbonyl moiety of the ligand lactone ring can convert an agonist into an antagonist and vice versa 42 . Consistent with these findings, substituting the lactone head group on the native AI with a phenyl head group converts the ligand into an antagonist 42,43 .…”
supporting
confidence: 56%
“…Among the set of mutants that we made, we identified one residue of interest: LasR S129. Previous work demonstrated that alteration of serine to alanine at this position transformed some LasR activators into inhibitors, and vice versa (32,33). Moreover, the LasR LBD structure suggests that S129 is part of the network that interacts with the ligand acyl chain (29).…”
Section: Resultsmentioning
confidence: 93%